Improved Vlasov Antenna with Curved Cuts and Optimized Reflector Position and Shape - H. M. El Misilmani; M. Al-Husseini; K. Y. Kabalan (International Journal of Antennas and Propagation)
This paper presents a Vlasov antenna with curved cut shape and improved reflector position and geometry suitable for high power microwave applications. The curved shape of the proposed cut totally eliminates the sharp edges and angles present in Vlasov antennas with step and bevel cuts. Furthermore, with the proposed reflector configuration, the wave is radiated in the direction of the axis of the waveguide. A Vlasov antenna, designed for operation at 3 GHz, is used to compare the three cut types. An additional comparison is conducted to validate the concept of the enhanced reflector position, using the bevel-cut antenna and the improved cut. The proposed antenna results in increased antenna gain and in good performance in terms of sidelobe level and half-power beamwidth, with maximum radiation directed toward the axis of the waveguide center.